Ketrampilan Pemasaran Digital Melalui Instagram Bagi Pelaku Usaha Souvenir Desa Pindaraya Kecamataan Simanindo Samosir - Romindo M Pasaribu; Vinsensius Matondang; Marco Sinaga (Yayasan Literasi Sains Indonesia, 2022)
Samosir Regency has potential in developing creative handicraft industries such as ulos weaving, woven pandanus, water hyacinth, carving, stone carving, pottery, bamboo crafts, screen printing, and Samosir specialties such as rondam beans and kopis losung. These handicraft products are local cultural wisdom and have high cultural values. Marketing through social media such as Instagram and the internet can help souvenir businesses in Pindaraya village to reach a wider market and even abroad. The purpose of this activity is to motivate Samosir souvenir business actors to use social media and the internet as a medium to promote their products and preserve Samosir's local culture to a wider market. The result of this activity is that the enthusiasm of the Samosir souvenir business is very high and has a commitment to using their Instagram social media as a marketing promotion tool. More use of the internet to look for marketing opportunities that they have not recognized and used. Instagram is one of the social media that is currently very much in demand by the people of Indonesia.